Por entre frestas do véu tecnológico: atitudes dos professores ante a formação continuada na escola - Tilger, Marcos Alexandre (2023)
The aim of this research was to identify and analyze teachers’ and pedagogical coordinators’ attitude toward typical activities and situations that occur in time allocated for in-service teacher training and its relationship with their attitudes of closure and openness to the experience and bildung. Thus, it resorted to the articulation between an integrative bibliographic review of theses and dissertations on the subject and an empirical research intermediated by concepts such as the Critical Theory of Society, undertaken with the use of Likert type scales. The critical attitude towards these processes was based on the theoretical contributions of Adorno, Horkheimer, Benjamin and Marcuse with emphasis on the concepts of technological rationality, halbbildung, experience, managed free time and Cultural Industry. Therefore, based on the statistical analysis of the results, it can be concluded that there are significant correlations between teachers’ attitudes and their expectations of attending certain typical situations and activities of continuous teacher training. The attitudes with higher factorial load associated with the closure for the formative experience showed to be more related to the desire to expand the time to perform motivational activities, the appropriation of new technological materials and training for the improvement of external results, while debates and studies related to the pedagogical practice and the school territory, in addition to participation in management, including demands for improvement in working conditions, they correlate more strongly with attitudes of openness to experience